Recombinant Factor VIII Fc Inhibits B Cell Activation via Engagement of the FcγRIIB Receptor - Georgescu, Maria T.; Moorehead, Paul C.; Liu, Tongyao; Dumont, Jennifer; Scott, David W.; Hough, Christine; Lillicrap, David (Frontiers in Immunology, 2020)
The development of neutralizing antibodies (inhibitors) against factor VIII (FVIII) is a major complication of hemophilia A treatment. The sole clinical therapy to restore FVIII tolerance in patients with inhibitors remains immune tolerance induction (ITI) which is expensive, difficult to administer and not always successful. Although not fully understood, the mechanism of ITI is thought to rely on inhibition of FVIII-specific B cells (1). Its efficacy might therefore be improved through more aggressive B cell suppression. FcγRIIB is an inhibitory Fc receptor that down-regulates B cell signaling when cross-linked with the B cell receptor (BCR). We sought to investigate if recombinant FVIII Fc (rFVIIIFc), an Fc fusion molecule composed of FVIII and the Fc region of immunoglobulin G1 (IgG1) (2), is able to inhibit B cell activation more readily than FVIII. rFVIIIFc was able to bind FVIII-exposed and naïve B cells from hemophilia A mice as well as a FVIII-specific murine B cell hybridoma line (413 cells). An anti-FcγRIIB antibody and FVIII inhibited binding, suggesting that rFVIIIFc is able to interact with both FcγRIIB and the BCR. Furthermore, incubation of B cells from FVIII-exposed mice and 413 cells with rFVIIIFc resulted in increased phosphorylation of SH-2 containing inositol 5-phosphatase (SHIP) when compared to FVIII. B cells from FVIII-exposed hemophilia A mice also exhibited decreased extracellular signal-regulated kinase (ERK) phosphorylation when exposed to rFVIIIFc. These differences were absent in B cells from naïve, non-FVIII exposed hemophilic mice suggesting an antigen-dependent effect. Finally, rFVIIIFc was able to inhibit B cell calcium flux induced by anti-Ig F(ab)2. Our results therefore indicate that rFVIIIFc is able to crosslink FcγRIIB and the BCR of FVIII-specific B cells, causing inhibitory signaling in these cells.